2016
DOI: 10.1152/ajprenal.00260.2015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of urinary angiotensinogen as a marker of podocyte injury in proteinuric nephropathies

Abstract: -Urinary protein (UP) is widely used as a clinical marker for podocyte injury; however, not all proteinuric nephropathies fit this model. We previously described the elevation of urinary angiotensinogen (AGT) accompanied by AGT expression by injured podocytes in a nitric oxide inhibition rat model (Eriguchi M, Tsuruya K, Haruyama N, Yamada S, Tanaka S, Suehiro T, Noguchi H, Masutani K, Torisu K, Kitazono T. Kidney Int 87: 116 -127, 2015). In this report, we performed the human and animal studies to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Although renal angiotensinogen is predominantly localized in the proximal tubules [ 44 , 46 , 47 ], weak expression is also detected in glomeruli. Since glomerular angiotensinogen is increased in damaged glomeruli [ 56 58 ], local RAAS activation in glomerulus may play a role in the pathophysiology of glomerular injury. Recently, Eriguchi et al [ 56 ] have shown that angiotensinogen is generated in injured glomerular podocytes in nephrotic rats induced by puromycin.…”
Section: Specific Role Of Angiotensinogen In the Regulation Of Ang IImentioning
confidence: 99%
See 3 more Smart Citations
“…Although renal angiotensinogen is predominantly localized in the proximal tubules [ 44 , 46 , 47 ], weak expression is also detected in glomeruli. Since glomerular angiotensinogen is increased in damaged glomeruli [ 56 58 ], local RAAS activation in glomerulus may play a role in the pathophysiology of glomerular injury. Recently, Eriguchi et al [ 56 ] have shown that angiotensinogen is generated in injured glomerular podocytes in nephrotic rats induced by puromycin.…”
Section: Specific Role Of Angiotensinogen In the Regulation Of Ang IImentioning
confidence: 99%
“…Since glomerular angiotensinogen is increased in damaged glomeruli [ 56 58 ], local RAAS activation in glomerulus may play a role in the pathophysiology of glomerular injury. Recently, Eriguchi et al [ 56 ] have shown that angiotensinogen is generated in injured glomerular podocytes in nephrotic rats induced by puromycin. These data suggest the potential contribution of podocyte angiotensinogen generation in the progression of proteinuria.…”
Section: Specific Role Of Angiotensinogen In the Regulation Of Ang IImentioning
confidence: 99%
See 2 more Smart Citations
“…Some have mixed origin; they can originate both in tubular cells and in podocytes, for example, angiotensinogen [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%